Migraine associated with altitude: results from a population‐based study in Nepal. (29th May 2017) - Linde, M.; Edvinsson, L.; Manandhar, K.; Risal, A.; Steiner, T. J.
Abstract : Background and purpose: A 1988 pilot study in Peru suggested an association between migraine and chronic exposure to high altitude. This study provides epidemiological evidence corroborating this. Methods: In a cross‐sectional nationwide population‐based study, a representative sample of Nepali‐speaking adults were recruited through stratified multistage cluster sampling. They were visited at home by trained interviewers using a culturally adapted questionnaire. The altitude of dwelling of each participant was recorded. Results: Of 2100 participants, over half [1100 (52.4%)] were resident above 1000 m and almost one quarter [470 (22.4%)] at ≥2000 m. Age‐ and gender‐standardized migraine prevalence increased from 27.9% to 45.5% with altitude between 0 and 2499 m and thereafter decreased to 37.9% at ≥2500 m. The likelihood of having migraine was greater (odds ratio, 1.5–2.2; P ≤ 0.007) at all higher altitudes compared with <500 m. In addition, all symptom indices increased with altitude across the range <500 m to 2000–2499 m, i.e. median attack frequency from 1.3 to 3.0 days/month ( P < 0.001), median duration from 9 to 24 h ( P < 0.001) and pain intensity [the proportion reporting 'bad pain' (highest intensity)] from 35.5% to 56.9% ( P = 0.011). Each of these showed a downward trend above 2500 m. Conclusions: Dwelling at high altitudes increases not only migraine prevalence but also the severity of its symptoms.